Malaysia’s strength in women leadership: success factor in localising the United Nations sustainable development goals - et. al., Shahnaz Shahizan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Countries worldwide pledged to achieve the targets of Sustainable Development Goals (SDG) introduced by the United Nation (UN) by the year 2030. Malaysia, amongst other developing countries, may need to focus on the localisation of the UN SDG led by women representatives, to ensure its success. This research aims to illustrate some of the many strengths that this country has, in achieving the successful localisation of the SDG, which is the existing knowledge of the SDG, and evidence of exhibited commitments to SDG related activities by selected women in focus group studies. Findings from a questionnaire distributed to 628 women representatives in Malaysia suggests substantiated SDG localisation efforts and prioritised goals according to the locality. With further examination on other strengths and weaknesses in the future, this research justifies reasons in entrusting women local leaders to ensure the successful implementation of the UN SDG in Malaysia and to be made a model for similar developing nations of the world.